The Papers and Writings of Abraham Lincoln $1 (BVolume 3: The Lincoln-Douglas Debatess - Lincoln, Abraham, 1809-1865; Lapsley, Arthur Brooks (Salt Lake City, UT : Project Gutenberg, 2004)
"The Papers and Writings of Abraham Lincoln $1 (BVolume 3: The Lincoln-Douglas$1! =(B" by Abraham Lincoln is a historical collection compiled in the mid-19th century. This volume includes important texts surrounding the renowned Lincoln-Douglas debates, particularly focusing on Lincoln's political speeches during the senatorial campaign of 1858 in Illinois. The central topic revolves around the contentious issue of slavery in America, as Lincoln articulates his views on its expansion and the moral and political ramifications it entails. At the start of this volume, the opening portion introduces Lincoln's speech delivered at Springfield, where he reflects on the escalating tensions surrounding slavery. He emphasizes the idea that the government cannot endure divided on the matter of slavery, famously stating, "A house divided against itself cannot stand." Lincoln presents a critical examination of recent legislative actions and court decisions, like the Nebraska Bill and the Dred Scott decision, asserting that these developments threaten the future of freedom and equality in America. He frames the political landscape as a pivotal moment of choice, urging his audience to recognize the urgency of addressing the issue of slavery before it crystallizes into a widespread injustice. (This is an automatically generated summary.)s
Release date is 2004-09-30
Produced by David Widger
Keywords: Lincoln-Douglas Debates, Ill., 1858